Rancang Bangun Fitur Pencarian Kontak Tamu Yang Tidak Diketahui Pada Webinvito Design Dengan Web Crawling Social Media Facebook - Nugraha, Chandra Satria; Lestari, Caecilia Citra (Jurnal Informatika dan Sistem Informasi, 2023)
Invitation is one of many media that is often used in an event making that is both formal and informal. To be able to send a paperless invitation by email or social media, we need the contacts to be able to send the invitation. A problem arises when a person doesn’t have the contact of people he wants to invite. One of the contact that can be used besides email is social media which one of the example is Facebook. Social media that is often used by people is Facebook. To be able to communicate with the other friend on Facebook, a relation is needed between one user and the others that is called friend. Besides that, Facebook users will have an automatically generated email that have Facebook.com extension. This feature design uses Snoopy as its crawler and Facebook API as data source to get user data. Feature consisted in five steps, from Query Input to define names to search for, Facebook User Search to find username from Facebook API, Name Checking to check the name of the Facebook user’s friend, Friend of Friend Crawling to find more about the Facebook user’s friend of friends from the next level, and Name Listing to make a list consist of the found Facebook user. There are two types for the testing, first is page load testing to find out whether the page will be slow when accessed by many users, second is friend search testing to find out which factor affects in search time. Page load testing gives result in between zero and two seconds. In friend search testing, upload speed affect the declaration of the crawler, while download speed affect the crawler speed doing friend of friend crawling. With the result of testing, friend search can use web crawling to find unknown friend contact.